أثر دلالة المكان في وعي الشاعر العربي في العصر الجاهلي: The pragmatic impact of ‘place’ on the awareness of the Arab poet in the pre-Islamic era - Owoyemi, Maruf Raji; Rahmah Binti Ahmad H. Osman ,; Muhammad Anwar Bin Ahmad, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يمثل "المكان" ميزة بارز من ميزات الشعر العربي الجاهلي، وكان له حضور بارز في إنتاجاتهم الشعرية، ولا يكاد يوجد شاعرا من شعراء العصر لجاهلي إلا وقد وقف على أطلال حبيبته أو يعشق إلى مرابعها وديارها التي عفت ويبكي إلى آثارها التي أكل عليها الدهر وشرب. وهو لا يقل أهمية في الشعر العربي، سواء كان المقصود به المعنى العام أو الخاص. وقد وظفه الشعراء الجاهليون توظيفا يشكل عنصرا من عناصر القصيدة العربية وتضفي عليها طوابع وجدانية نفسية ترتسم إليها الذكريات. ويهدف هذا البحث إلى دراسة دلالة المكان في الشعر الجاهلي تحديدا في المعلقات الشعرية من خلال ربط المكان بنصوص المعلقات الشعرية التي تناولت الأماكن في العصر الجاهلي. وقد يظن بعض الناس أن المكان – بمعناه العام والخاص – يرمز إلى مجرد سكن أو موقع جغرافي غير أنه يرمز إلى معان أعمق وبعد خيالي نفسي ووجداني حيث يفيضه علي الإنسان من روح المواطنة والكينونة وهو من أهم المظاهر الجمالية، وله ارتباط وثيق بالوجود والكينونة، والهوية الإنسانية، مما يستدعي منا الاهتمام به. وكان لهذه الدراسة أهمية بالغة حيث أنه تعتمد على المنهج الوصفي التحليلي لمعالجة قضايا المكان ووصفه ودلالته في الشعر العربي الجاهلي. ومن أهم نتائج الدراسة أن هناك علاقة تفاعلية بين المكان وساكنه حيث تجعل المكان واضحا في تشكيل النص، وهذا ما نجده في الشعر الجاهلي، وكما نلاحظ أن رحابة المكان جغرافيا لا تعني بالضرورة اتساعه في الشعر أو في نفسية شخوصها خاصة. ABSTRACT “Place” represents a prominent feature of pre-Islamic Arab poetry, and it has presence in their poetic productions. Hardly would you find a poet of the pre-Islamic era without standing on the ruins of his beloved, craving for the depastures of her ruined homes, and criing for his beloved that has been consumed by time. “Place” is no less important in Arabic poetry, whether within the contextual or literal meaning. The pre-Islamic poets used it in a way that constitutes an element of the Arabic poem and gives it emotional and psychological stamps that bring back memories. This research, therefore, aims to study the significance of place in pre-Islamic poetry, specifically in poetic appreciation, by linking place to the texts of poetic appreciation that dealt with places in the pre-Islamic era. Some people may think that “place” - in its general and specific sense - symbolizes mere habitation or a geographical location, but it symbolizes deeper meanings and an imaginative, psychological and emotional dimension, as it overflows upon a person with the spirit of citizenship and being. It is one of the most important aesthetic manifestations, and has a close connection to existence, being, and human identity. Which requires us to pay attention to it. This study was of great importance as it relied on the descriptive and analytical approach to address issues of place, its description, and its significance in pre-Islamic Arabic poetry. The main finding of the study is that there is an interactive relationship between the “place” and its inhabitant, which makes the place clear in the formation of the text, and this is what we find in pre-Islamic poetry. As we note, the geographical spaciousness of the place does not necessarily mean its breadth in poetry or in the psychology of the poet in particular.